A mixed methods analysis of lithium-related patient safety incidents in primary care - Richard Simon Young; Paul Deslandes; Jennifer Cooper; Huw Williams; Joyce Kenkre; Andrew Carson-Stevens (SAGE Publishing, 2020)
Background: Lithium is a drug with a narrow therapeutic range and has been associated with a number of serious adverse effects. This study aimed to characterise primary care lithium-related patient safety incidents submitted to the National Reporting and Learning System (NRLS) database with respect to incident origin, type, contributory factors and outcome. The intention was to identify ways to minimise risk to future patients by examining incidents with a range of harm outcomes. Methods: A mixed methods analysis of patient safety incident reports related to lithium was conducted. Data from healthcare organisations in England and Wales were extracted from the NRLS database. An exploratory descriptive analysis was undertaken to characterise the most frequent incident types, the associated chain of events and other contributory factors. Results: A total of 174 reports containing the term 'lithium' were identified. Of these, 41 were excluded and, from the remaining 133 reports, 138 incidents were identified and coded. Community pharmacies reported 100 incidents (96 dispensing related, two administration, two other), general practitioner (GP) practices filed 22 reports and 16 reports originated from other sources. A total of 99 dispensing-related incidents were recorded, 39 resulted from the wrong medication dispensed, 31 the wrong strength, 8 the wrong quantity and 21 other. A total of 128 contributory factors were identified overall; for dispensing incidents, the most common related to medication storage/packaging ( n  = 41), and 'mistakes' ( n  = 22), whereas no information regarding contributory factors was provided in 41 reports. Conclusion: Despite the established link between medication packaging and the risk of dispensing errors, our study highlighted storage and packaging as the most commonly described contributory factors to dispensing errors. The absence of certain relevant data limited the ability to fully characterise a number of reports. This highlighted the need to include clear and complete information when submitting reports. This, in turn, may help to better inform the further development of interventions designed to reduce the risk of incidents and improve patient safety. Lay Summary A characterisation of lithium-related patient safety incidents in primary care Lithium is an effective treatment for certain mental illnesses, but has a number of harmful side effects. Safety incidents related to medicines in the UK are reported to the National Reporting and Learning System database (NRLS), and concerns relating to lithium have previously been highlighted. This study aimed to characterise lithium incidents reported to the NRLS that occurred in a primary care setting. Reports relating to lithium and submitted between 2002 and 2013 were reviewed, and the information coded. A total of 174 reports containing the term 'lithium' were identified. Of these, 41 were excluded and, from the remaining 133 reports, 138 incidents were identified and coded with respect to incident origin, type, contributory factors and outcome. A total of 100 incidents were reported by community pharmacies (96 of which related to medicine dispensing), general practitioner (GP) practices filed 22 reports and 16 reports originated from other sources. Of the dispensing-related incidents, 39 resulted from the wrong medication dispensed, 31 the wrong strength, 8 the wrong quantity and 21 other. A total of 128 contributory factors were identified overall; for dispensing incidents, the most common related to medication storage/packaging ( n  = 41), and 'mistakes' ( n  = 22) whereas no information regarding contributory factors was provided in 41 reports. Despite the established link between medication packaging and the risk of dispensing errors, our study highlighted storage and packaging as the most commonly cited contributory factors to dispensing errors. The absence of certain relevant data limited the ability to fully characterise a number of reports. This highlighted the need to include clear and complete information when submitting reports. This, in turn, may help to better inform the further development of interventions designed to reduce incident numbers and improve patient safety.